“AUGMENTATIVE INTELLIGENCE” SEBAGAI PEDAGOGI KATEKETIK KONTEKSTUAL: REKONSTRUKSI KEARIFAN LOKAL KEPULAUAN MALUKU DI ERA AI - Dr. Bruno Rumyaru, SS., MA (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2026)
The rapid development of Artificial Intelligence (AI) has significantly transformed the fields of education and catechesis, while simultaneously presenting challenges related to contextuality and the preservation of local cultural values. This article explores the concept of Augmentative Intelligence as a contextual catechetical pedagogy that harmonizes AI technology with the local wisdom traditions of the Maluku Islands. Using a literature review method and a reflective-theological approach, the study examines the interconnections between digital pedagogy, the theology of inculturation, and core Malukan cultural values such as pela-gandong, masohi, Larwul Ngabal, Duan-Lolat, and the family or clan system. The study reveals that AI can function augmentatively by fostering dialogue in faith formation, supporting cultural transmission, and encouraging participatory and humanistic catechetical learning. Consequently, Augmentative Intelligence provides an inculturative, contextual, and relevant catechetical model for the Church in responding to the challenges of the digital era.